Combination of Bacillus tequilensis with difenoconazole to control pear black spot and the related synergistic mechanism - Bi, Qiuyan; Lu, Fen; Wu, Jie; Liu, Xiangyu; Han, Xiuying; Wang, Wenqiao; Zhao, Jianjiang (Frontiers in Microbiology, 2024)
Background: Pear black spot (PBS) is caused by Alternaria alternata and causes severe damage worldwide. It is particularly important to screen for synergistic fungicide combinations to address issues associated with the low efficacy of biocontrol agents, high dosage requirements and poor sustained effectiveness of chemical fungicides.In vitro and in vivo studies were performed to determine the efficacy of a treatment for this important disease. Additionally, transcriptomic and metabolomic analyses were performed to determine the main molecular and biochemical mechanisms involved in the interaction.Results: Bacillus tequilensis 2_2a has a significant synergistic effect with difenoconazole, causing hyphal entanglement and spore lysis and inhibiting the formation of PBS lesions in vitro. In the field, the control effect of the combination was greater than 95%. The pathways associated with the synergistic effect on the mycelia of A. alternata were divided into two main types: one included glycolysis, oxidative phosphorylation, and MAPK signal transduction, while the other included glycolysis, the TCA cycle, coenzyme A biosynthesis, sterol synthesis, and fatty acid degradation. Both types of pathways jointly affect the cell cycle. The main functions of the key genes and metabolites that have been verified as being affected are glucose synthesis and oxidative respiration, as well as citric acid synthesis, acetyl-CoA synthesis, and sterol synthesis. Both functions involve intracellular pyridine nucleotide metabolism and adenine nucleotide transformation.This study helps to reveal the synergistic mechanisms underlying the combined efficacy of biological and chemical agents, providing a scientific basis for field applications.